(untitled) (The Review of Diabetic Studies, 2025)
At the national level, the evaluation and management of leprosy eradication program effectiveness primarily rely on the documentation of grade-2 disabilities. However, for effective prevention of disabilities, the assessment and management of grade-1 conditions hold greater significance. This is due to the fact that impairment of nerve function, whether sensory, motor, or both, generally manifests prior to the appearance of the visible deformities associated with grade-2 disabilities. Consequently, individuals diagnosed with grade-2 disabilities must have previously encountered grade-1 conditions. Therefore, when assessing any case of leprosy, it is crucial to conduct a comprehensive neurological examination of the peripheral nerves, and treatment strategies should be integrated from the stage of grade-1 disability itself. In order to attain comprehensive rehabilitation, the main emphasis must be placed on addressing the physical disabilities resulting from leprosy, whereas the secondary emphasis should be on tailoring lifestyle adjustments for the patients, their families, and their communities. The rehabilitation process for those affected by leprosy should commence at the time of diagnosis and persist until the patient is capable of leading a completely active and normal life.